Immunity waning after COVID vaccine booster vs. infection—better than expected. Issue 11 (2nd November 2022) - Khoury, Johad; Najjar-Debbiny, Ronza; Elemy, Ameer; Jabbour, Adel; Haj, Juliana; Abu-Sini, Majdolen; Yasin, Rabah; Amin, Mohammad; Hellou, Elias; Nasrallah, Najib; Saffouri, Amer; Hakim, Fahed
Abstract: Background: Rapid decline in antibody-titres after BNT162b2 mRNA COVID-19 vaccine was reported; thus, a booster dose, and recently a second booster were approved. The study aims to discuss immunogenicity throughout the pandemic, especially after booster dose. Methods: A prospective study conducted in EMMS-Nazareth hospital, Israel. Anti-SARS-CoV-2 IgG antibody titres were monitored every 5 weeks starting from the vaccine's second dose. To detect symptomatic and asymptomatic infections, nasopharyngeal swabs for COVID-19 PCR were obtained bi-weekly, and on suggestive symptoms. Third dose of the vaccine was suggested for all participants 5 months after the second one. A comparison was made between those who received three doses (booster-group), and those who were infected after having two doses (infection-group) or three doses (booster-infection) group. Results: One-hundred participants were included; 66 finished 14 months of follow-up, out of whom 40 received a third dose, 10 received only two doses—all were infected (mean time for infection 5 ± 12.15 weeks before the designated booster), and 12 received three doses and were infected. The mean titres of these three groups 7 months after the designated booster dose (regardless of receiving it) were 1756 ± 2279; 3483 ± 3016 and 6925 ± 3720 BAU/mL, respectively. The booster group had high titres 7 months after the booster dose, comparable to two months after the second dose ( p = .69); The booster-infected group had even higher titres. Conclusion: Immunogenicity decline rate after the booster dose is slower than the second dose. Timing of second booster in general population is still to be determined; neutralizing-antibody titres might be helpful.